Regional Clustering with Account of the Urban Life Support Enterprises - Dymchenko Olena V.; Smachylo Valentyna V.; Rudachenko Olhа O.; Khailo Yana M. (Bìznes Inform, 2023)
The publication examines the problems of housing and communal services, which consist in the unprofitable operation of housing and communal services enterprises, significant amounts of receivables and payables, outdated equipment and lack of finance for their modernization, etc. Potential participants and directions of socioeconomic development in the form of a «Regional Cluster of Urban Life Support Enterprises» are formed. The authors propose to integrate urban life support enterprises into a corporation of utilities of water supply, sewerage and heat supply, which will consist of combining: the enterprises from other sectors; the areas of intellectual development, the enterprises for diversification of services; the regional water refinement complexes; the grouped water supply enterprises; and a municipal information and analytical enterprise. It is noted that in the developed countries of the European Union there is a significant number (more than 2 thousand) of quite similar clusters, and up to 100 countries have programs for creating clusters today. Strategic ways for further work on the formation of such cluster formations for urban life support enterprises of Ukrainian cities have been elaborated. These include: 1. Identification of strategic directions of reform and development. 2. Innovative development of management processes. 3. Innovative development of management technology. 4. Innovative development of the enterprise management system. 5. Development of methods of information and analytical support of enterprise management. 6. Proposal of innovative methods and measures for diversification and integration of activities. 7. Proposal of restructuring models. 8. Proposal of models of the public-private reform. 9. Proposal of models of socioeconomic and intellectual clusters as a strategy for innovative development of both the enterprise and the region. 10. Proposal of individual innovative projects (measures) in the sphere of production and commerce to improve financial and economic sustainability and production-economic reliability.